2018
DOI: 10.1111/cas.13734
|View full text |Cite
|
Sign up to set email alerts
|

Double‐negative feedback interaction between DNA methyltransferase 3A and microRNA‐145 in the Warburg effect of ovarian cancer cells

Abstract: Ovarian cancer is the most lethal gynecological malignancy because of its poor prognosis. The Warburg effect is one of the key mechanisms mediating cancer progression. Molecules targeting the Warburg effect are therefore of significant therapeutic value for the treatment of cancers. Many microRNAs (miR) are dysregulated in cancers, and aberrant miR expression patterns have been suggested to correlate with the Warburg effect in cancer cells. In our study, we found that miR‐145 negatively correlated with DNA met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 37 publications
4
51
0
Order By: Relevance
“…We revealed miR-145 inhibited aerobic glycolysis through targeting HK2, and miR-145 downregulated PKM2 expression in our previous study; however, the specific mechanism remained unclear (Zhang et al, 2018). We found that miR-145 could upregulate the miR-133b mRNA level (Figure 2a).…”
Section: Upregulated Mir-133b Mediated Inhibitory Activity Of Mir-1mentioning
confidence: 63%
See 2 more Smart Citations
“…We revealed miR-145 inhibited aerobic glycolysis through targeting HK2, and miR-145 downregulated PKM2 expression in our previous study; however, the specific mechanism remained unclear (Zhang et al, 2018). We found that miR-145 could upregulate the miR-133b mRNA level (Figure 2a).…”
Section: Upregulated Mir-133b Mediated Inhibitory Activity Of Mir-1mentioning
confidence: 63%
“…We have demonstrated that miR‐145 increased miR‐133b expression on a methylation level, and confirmed miR‐145 regulated PKM2 through miR‐133b. In our previous research, we showed that miR‐145 and DNMT3A formed negative feedback pathways (Zhang et al, ). In addition, we demonstrated that miR‐145 upregulated miR‐133b expression by targeting DNMT3A and c‐myc, thus downregulating the methylation level of the miR‐133b promoter region.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In recent years, the regulatory role of miR-145 in tumor metabolism has been paid more and more attention. In our previous studies, we found that miR-145 regulates Warburg effect by targeting HK2 (Zhang et al, 2018b). However, whether miR-145 is involved in glutamine metabolism and the clear molecular mechanism is not fully known.…”
Section: Discussionmentioning
confidence: 96%
“…In osteosarcoma, micelleplexes containing miR‐145 are used to suppress cell proliferation and migration . In ovarian cancer, the negative feedback loop of DNMT3A and miR‐145 can affect the Warburg effect of cells . MiR‐145 has also been used to treat prostate cancer metastasis .…”
Section: Introductionmentioning
confidence: 99%